Review of Intellectual Capital Components Research - Alkhateeb, Abdullah N. A.; Liu, Yao; Cheng, Jack Kie (JASR, 2018)
The success of the organizations in a competitive business environment is depending on the intellectual capital, which is considered as strategic assets for sustainability of the organization. In the knowledge-based economy, modern and high tech organizations not only concentrate on innovation, services, marketing, research and development, instead pay particular attention to the organization intellectual capital. The aim of this paper is to investigate theoretically and empirically contributions in the subject of intellectual capital in an endeavor to recognize the components of intellectual capital. However, to achieve the objective of this paper a comprehensive related literature review was performed. The related literature showed that there are nine dimensions of intellectual capital that have been identified.